Ed Wood - Burton, Tim, 1958-; Depp, Johnny; Martin Landau (USA Touchstone Pictures, 1994)
The life of Edward D. Wood,Jr, hailed as the worst director (of 'Plan 9 From Outer Space', 'Glen or Glenda?' and 'Bride of the Monster') of all time.
The mostly true story of the legendary director of awful movies and his strange group of friends and actors.
Rudolph Grey
Languages : English, Spanish Subtitles : English, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian
Keywords: Comedy; Drama; Biography